Impact of the COVID‐19 pandemic on interventional cardiology fellowship training in the New York metropolitan area: A perspective from the United States epicenter. Issue 2 (16th May 2020) - Gupta, Tanush; Nazif, Tamim M.; Vahl, Torsten P.; Ahmad, Hasan; Bortnick, Anna E.; Feit, Frederick; Jauhar, Rajiv; Kandov, Ruben; Kim, Michael; Kini, Annapoorna; Lawson, William; Leber, Robert; et al.
Abstract: Background: The healthcare burden posed by the coronavirus disease 2019 (COVID‐19) pandemic in the New York Metropolitan area has necessitated the postponement of elective procedures resulting in a marked reduction in cardiac catheterization laboratory (CCL) volumes with a potential to impact interventional cardiology (IC) fellowship training. Methods: We conducted a web‐based survey sent electronically to 21 Accreditation Council for Graduate Medical Education accredited IC fellowship program directors (PDs) and their respective fellows. Results: Fourteen programs (67%) responded to the survey and all acknowledged a significant decrease in CCL procedural volumes. More than half of the PDs reported part of their CCL being converted to inpatient units and IC fellows being redeployed to COVID‐19 related duties. More than two‐thirds of PDs believed that the COVID‐19 pandemic would have a moderate (57%) or severe (14%) adverse impact on IC fellowship training, and 21% of the PDs expected their current fellows' average percutaneous coronary intervention (PCI) volume to be below 250. Of 25 IC fellow respondents, 95% expressed concern that the pandemic would have a moderate (72%) or severe (24%) adverse impact on their fellowship training, and nearly one‐fourth of fellows reported performing fewer than 250 PCIs as of March 1st. Finally, roughly one‐third of PDs and IC fellows felt that there should be consideration of an extension of fellowship training or a period of early career mentorship after fellowship. Conclusions: The COVID‐19 pandemic has caused a significant reduction in CCL procedural volumes that is impacting IC fellowship training in the NY metropolitan area. These results should inform professional societies and accreditation bodies to offer tailored opportunities for remediation of affected trainees.